1987
DOI: 10.1111/j.1471-4159.1987.tb05672.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Monosodium Glutamate Causes Long‐Lasting Cholinergic and Adrenergic Changes in Various Brain Regions

Abstract: Prenatal monosodium glutamate (MSG) given through the mother's diet was found previously to cause behavioral changes in the offspring, including learning disabilities. In the present study, neurochemical parameters were measured in the brains of prenatally exposed rats at various ages throughout development up to adulthood. At 15 days of age, choline uptake and choline acetyltransferase (ChAT) activity in the frontal cortex were significantly reduced (by 80 and 25%, respectively) in MSG-exposed animals, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…In a second study from this group [19], they gave MSG in drinking water at the same concentration as in their previous study to gravid Wistar rats on the same gestational days (the last 14 days of pregnancy up to E20) as before. The outcomes assessed in this experiment were 3 H-choline, norepinephrine (NE), and GABA (gammaamino butyric acid) uptake into selected brain regions in synaptosomal fractions, and 14 C-acetyl-CoA uptake, as a marker of choline acetyltransferase activity, in crude fractions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a second study from this group [19], they gave MSG in drinking water at the same concentration as in their previous study to gravid Wistar rats on the same gestational days (the last 14 days of pregnancy up to E20) as before. The outcomes assessed in this experiment were 3 H-choline, norepinephrine (NE), and GABA (gammaamino butyric acid) uptake into selected brain regions in synaptosomal fractions, and 14 C-acetyl-CoA uptake, as a marker of choline acetyltransferase activity, in crude fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies were done in Wistar rats, exposing them to MSG in their drinking water during the last 2 weeks of gestation [18,19]. In the first study [18], MSG was provided as 5 g/100 mL of water resulting in an estimated dose of 10 g/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the endpoints tested were in an experimental stage and were never included in later OECD protocols for neurodevelopmental toxicity testing [59], because of a high degree of variability, leading eventually to the conclusions that these findings do not exhibit a pattern of developmental neurotoxicity (Vorhees et al [3], this issue). In addition, other reproductive and (neuro)developmental toxicity studies reveal higher NOAEL values, including the highest dose level tested of 6,000 mg/kg bw/day in the 3-generation reproductive toxicity study in mice as the most sensitive species reported by Anantharaman [47] that also performed extensive histopathology of brain tissue, and the only dose tested of 10,000 mg/kg bw/day in the developmental neurobehavior study reported by Frieder and Grimm [55,56] on which the EFSA concluded that there were no adverse effects when corrected for multiple testing. Considering the study of Vorhees et al [3] to be inappropriate for human risk assessment, these other studies provide a point of departure that is higher than 6,000 mg/kg bw/day and perhaps even higher than 10,000 mg/kg bw/day.…”
Section: Hazard Identification and Assessmentmentioning
confidence: 99%
“…Frieder and Grimm [113,114] have demonstrated that feeding MSG to pregnant rats can lead to severe alterations in learning that only affected the male rats, again demonstrating a male preponderance of toxic effects. It has also been shown that sensitivity to glutamate increases after birth [115,116].…”
Section: Effect Of Dietary Food Additive Excitotoxinsmentioning
confidence: 99%
“…Of great concern is the finding of MartinezContreras et al [119] that glutamate can prime microglia, leading to brain inflammation and high levels of inflammatory cytokines in the brain. In addition, some studies [114,120] have demonstrated alteration in hippocampal architecture and synaptic development following neonatal exposure to MSG in animal models.…”
Section: Effect Of Dietary Food Additive Excitotoxinsmentioning
confidence: 99%